Antecedents And Outcome Of Earnings Management In Iraqi Listed Firms: Corporate Social Responsibility As Moderator - Ahmed, Mohammed Ghanim (2023)
This research investigated (i) the corporate governance mechanism (board independence, board tenure, audit committee, internal audit function, board meeting frequency, and female board member) impacts on earnings management and organizational performance in Iraqi listed firms under the agency theory and (ii) the effect of corporate social responsibility (CSR) as a moderating role under the stakeholder theory among 65 firms ranging between the financial years of 2013 and 2018.